Unraveling the strain and inherent onsite-correlation effect on the electronic structure of pure and iso-electronic Ag doped copper nitride. (December 2022) - Sahoo, Guruprasad; Jena, Ajit
Abstract: Promising optoelectronic properties of semiconducting copper nitride (Cu3 N), have brought the material into limelight for numerous device applications. As band gap (Eg ), undoubtedly is a key parameter in determining proficiency of a semiconductor in optoelectronics, hence its modulation needs clear understanding both from the fundamental and application perspectives. The present study discusses the impact of inherent onsite Coulomb-correlation (through Hubbard U) and strain on the electronic properties of pure and iso-electronic element (Ag) doped Cu3 N using density functional calculations. A slow rate of increase in Eg with U recognizes Cu3 N a weakly correlated system. Alternately, U for the doped system (Cu2 AgN) is discovered to have further weaker effect on the Eg, nearly independent for U > 2 eV. However, doping of the 4 d electronic element in the 3 d transition metal nitride predicts an increased carrier mobility which will subsequently improve electrical conductivity. While examining the effect of strain in pristine Cu3 N, the lowest conduction band is found to have both approaching and avoiding feature with respect to the Fermi level at two different high symmetry k -points. Consequently, Eg decreases (increases) for the compressive (tensile) strain which is attributed to the higher (lower) dispersive nature of the valence bands due to stronger (weaker) p-d hybridization. In case of Cu2 AgN, though a similar shifting in the lower conduction band is observed, the variation of Eg with strain is quite different to that of Cu3 N. While Eg increases (decreases) for the uniaxial compressive (tensile) strain, it decreases both for tensile and compressive strains corresponding to the isotropic deformations. Graphical Abstract: ga1 Highlights: Effect of onsite Coulomb correlation and strain on electronic properties of pure and Ag doped Cu3 N has been investigated. Cu3 N is recognized as a weakly correlation system and Ag doping leads to further weaker correlation effect. Band gap of Cu3 N decreases (increases) for the compressive (tensile) strain which is attributed to stronger (weaker) p-d hybridization. A dissimilar variation of the band gap with strain is observed for the Ag doped system.